GTPase GPN3 facilitates cell proliferation and migration in non-small cell lung cancer by impeding clathrin-mediated endocytosis of EGFR - Linlin Xu; Jiankun Guo; Xinsheng Xie; Hailong Wang; Alan Jiang; Changhua Huang; Hua Yang; Shiwen Luo; Limin Chen (Cell Death Discovery)
Abstract Small GTPases play a critical role as regulatory molecules in signaling transduction and various cellular processes, contributing to the development of human diseases, including cancers. GPN3, an evolutionarily conserved member of the GPN-loop GTPase subfamily classified in 2007 according to its structure, has limited knowledge regarding its cellular functions and molecular mechanisms. In this study, we demonstrate that GPN3 interacts with clathrin light chain A (CLTA), a vesicle coat protein, as well as clathrin-mediated endocytosis associated modulators AP2B1 and AP2S1. Upregulation of GPN3 leads to the inhibition of clathrin-coated pit invagination. Furthermore, we discovered that GPN3 interacts with the epidermal growth factor receptor (EGFR) and regulates the co-localization of EGFR and CLTA, as well as the localization of EGFR in early endosomes upon EGF stimulation. As a result, this leads to a decrease in endocytic levels of EGFR and an increase in the accumulation of EGFR on the cell membrane surface, thereby prolonging activation of EGFR signaling. The functional effects exerted by GPN3 are dependent on cellular levels of GTP abundance. Furthermore, our findings indicate that aberrant overexpression of GPN3 is observed in non-small cell lung cancer (NSCLC) tissues compared to adjacent normal tissues, and high expression levels of GPN3 are associated with poor prognosis for NSCLC patients. Collectively, these findings reveal that GPN3 acts as an oncogene promoting cell proliferation and migration in NSCLC through regulation of clathrin-dependent EGFR endocytosis. These results suggest that targeting GPN3 could serve as a novel prognostic biomarker and therapeutic strategy for NSCLC treatment.